Integrating Scenario Planning and Cost-Benefit Methods - Aldrich, Stephen C. (The Hastings Center report, 2018)
By their nature, the most vexing social problems reflect collisions between social and economic interests of parties with highly divergent views and perspectives on the cause and character of what is at issue and the consequences that flow from it. Conflicts around biotechnology applications are good examples of these problems. When considering the potential consequences of proposed biotechnology applications, an enormous range of perspectives arise reflecting the breadth of different and often competing interests with a stake in life's future. This essay starts from an assumption that the traditional tool of cost-benefit analysis is not adequate for adjudicating competing claims around the introduction of new biotechnology applications. It tends to require implicit simplifying assumptions that reduce or mask true underlying levels of complexity and uncertainty, and the results it produces deliver a definitive and singular answer, as opposed to a multiplicity of outcomes. In this essay, I describe some of the key elements of formal scenario planning to show how CBA could be redeployed as a supporting tool within the broader decision support methodology of formal scenario planning.